Experience report: implementing requirement traceability throughout the software development life cycle. Issue 11 (November 2016) - Akman, Suha; Özmut, Mert; Aydın, Burak; Göktürk, Serhat
Abstract: The developed traceability model is essential in helping project members, project managers and customers, all understand the product at all stages of the software development life cycle and maintain the integrity of the design information. Utilizing a well designed development environment and an environment support team is vital in maintaining the requirement traceability. With the requirement traceability, the customers' requirement status can be monitored and the relationships among requirements, design decisions, and code can be accessed to reuse already developed products or analyze the change impacts, which in turn benefits companies by lowering the development and maintenance cost. This paper describes how requirement traceability is supported in an information technology solution provider company, with the improvement of integrated tool infrastructure, the transformation of the tool infrastructure, and the challenges that were faced during the transformation. Throughout this improvement project, not only the tools and their capabilities were looked into but also the company culture and the already acquired know‐how in using many infrastructure tools such as Enterprise Project Management, JIRA, Team Foundation Server, Quality Center, Enterprise Architect, SVN, and Eclipse. Abstract : Requirements traceability support and infrastructure in development environments are essential in helping project members, project managers, and customers; all understand the product at all stages of the software development life cycle and assess the impact of changes. Benefits increase as the system size, complexity, or project members increase.